New Insights Into Gut-Bacteria-Derived Indole and Its Derivatives in Intestinal and Liver Diseases - Li, Xiaojing; Zhang, Binbin; Hu, Yiyang; Zhao, Yu (Frontiers in Pharmacology, 2021)
The interaction between host and microorganism widely affects the immune and metabolic status. Indole and its derivatives are metabolites produced by the metabolism of tryptophan catalyzed by intestinal microorganisms. By activating nuclear receptors, regulating intestinal hormones, and affecting the biological effects of bacteria as signaling molecules, indole and its derivatives maintain intestinal homeostasis and impact liver metabolism and the immune response, which shows good therapeutic prospects. We reviewed recent studies on indole and its derivatives, including related metabolism, the influence of diets and intestinal commensal bacteria, the targets and mechanisms in pathological conditions, especially progress in therapeutic strategies. New research insights into indoles will facilitate a better understanding of their druggability and application in intestinal and liver diseases.